The nutmeg of consolation - O'Brian, Patrick, 1914-2000 (O'Brian, Patrick, 1914-2000. Aubrey/Maturin novels, 1992)
Shipwrecked on a remote island in the Dutch East Indies, Captain Aubrey, surgeon and secret intelligence agent Stephen Maturin, and the crew of the Diane fashion a schooner from the wreck. A vicious attack by Malay pirates is repulsed, but the makeshift vessel burns, and they are truly marooned. Their escape from this predicament is one that only the whimsy and ingenuity of Patrick O'Brian - or Stephen Maturin - could devise.